The Effects of Resistance Training on Physical Fitness and Neuromotor-Cognitive Functions in Adults With Down Syndrome - Post, Emily M.; Kraemer, William J.; Kackley, Madison L.; Caldwell, Lydia K.; Volek, Jeff S.; Sanchez, Barbara N.; Focht, Brian C.; Newton, Robert U.; Häkkinen, Keijo; Maresh, Carl M. (Frontiers in Rehabilitation Sciences, 2022)
Adults with Down syndrome are an underserved population at high risk for a host of different pathologies from aging and lack of activity. Purpose To examine the effects of a 10-week resistance training program on measures of motor behavior, cognitive function, mood, and physical fitness. Methods Participants (n = 11) were men and women clinically diagnosed with Down syndrome (age: 25.8 ± 6.4 years; height: 151.5 ± 8.3 cm; weight: 67.5 ± 13.0 kg; IQ: 58.3 ± 19.7 units). After familiarization of testing procedures, subjects performed The Arizona Cognitive Test Battery for Down Syndrome, TGMD-2, lower and upper body strength assessments, and body composition via DXA testing, while parental guardians completed cognitive and mood survey assessments (Cognitive Scale for Down Syndrome, Behavioral Rating Inventory of Executive Function, NiSonger Child Behavior Rating Form, Scales of Independent Behavior-Revised, Child Eating Behavior Questionnaire, Social Communication Questionnaire, and Mood and Feelings Questionnaire) at pre and post 10 weeks of periodized resistance training. Results Significant (P ≤ 0.05) improvements in locomotor skills and object control skills were observed post-training. Both locomotor skills (e.g., sprint, gallop, leaping, broad jump) and object control skills (e.g., baseball catch, underhand roll, basketball dribble) were all significantly improved. Facets of cognitive performance significantly improved, specifically executive function and visuospatial working memory capacity, and frontal lobe activity. Mood disturbances significantly decrease. All aspects of physical strength and endurance were improved, i.e., leg press, bench press, sit-ups, push-ups, and chair sit-to-stand post-training. Lean tissue mass was significantly increased post-training. Conclusion This study dramatically demonstrates that life enhancements for individuals with Down syndrome are achievable with a properly designed resistance training program.